Analyzing Key Success Factors for Driving Repurchasing Conversion in E-CRM: Customer Insights on Gojek Application in Batam - Limanda, Mellberg; Eryc; Deu, Indasari (LPPM Universitas Bhinneka Nusantara, 2026)
This study examines the determinants of repurchase intention in Gojek’s digital service environment by integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), with Customer Relationship Management (CRM) serving as the contextual framework. In this study, CRM is not operationalized as an independent variable but provides the contextual setting for understanding user interactions with the platform. Using a sequential mixed-methods design, Qualitative findings reveal that price sensitivity is the most dominant factor influencing repurchase decisions for key drivers of repurchase intention, followed by usability, functional efficiency, and trust. Quantitative analysis via Partial Least Squares Structural Equation Modeling (PLS-SEM) confirmed that Perceived Ease of Use significantly influences Perceived Usefulness, which shapes Attitude, while Attitude and Perceived Behavioral Control strongly predict Repurchase Intention; Subjective Norms exert a weaker effect. By positioning CRM as a contextual environment rather than a measured construct, this study extends the application of the TAM–TPB framework in digital ride-hailing services and provides practical insights for strengthening customer retention strategies.